Control of the Actin Cytoskeleton Within Apical and Subapical Regions of Pollen Tubes - Xu, Yanan; Huang, Shanjin (Frontiers in Cell and Developmental Biology, 2020)
In flowering plants, sexual reproduction involves a double fertilization event, which is facilitated by the delivery of two non-motile sperm cells to the ovule by the pollen tube. Pollen tube growth occurs exclusively at the tip and is extremely rapid. It strictly depends on an intact actin cytoskeleton, and is therefore an excellent model for uncovering the molecular mechanisms underlying dynamic actin cytoskeleton remodeling. There has been a long-term debate about the organization and dynamics of actin filaments within the apical and subapical regions of pollen tube tips. By combining state-of-the-art live-cell imaging with the usage of mutants which lack different actin-binding proteins, our understanding of the origin, spatial organization, dynamics and regulation of actin filaments within the pollen tube tip has greatly improved. In this review article, we will summarize the progress made in this area.